Determinants of product upgrading in Seka Chekorsa District, Jimma Zone, Oromia Region, Ethiopia - Zalalam Lule; Mekdelawit Yeshitila; Mulubrihan Bayissa (Cogent Business & Management, 2024)
Product upgrading is the most viable solution for small holder farmers to increase their income and capture more of the value of their product in the value chain. This paper was aimed at assessing factors affecting smallholder tomato producers' participation decisions in product upgrading (adopting improved variety, pesticide application, and staking). Qualitative and quantitative data were collected from primary and secondary sources of data. Semi-structured interview, focus group discussion, key informant interview, and personal observation were used to collect data. To analyse data obtained from sample respondents, descriptive and econometric models (multivariate probit model) were used. The result of the study implied that family size, farming experience, year of school, access to market information, training, seed, and pesticide significantly and positively influenced one or more product upgrading techniques while age and market distance had negative and significant association with product upgrading. Therefore, policy and development interventions should give emphasis towards the improvement of such institutional support system so as to foster household participation in product upgrading.
Keywords: 650; Ethiopia; improved variety adoption; multivariate probit; pesticide application; product upgrading; staking